THE EFFECT OF LIVE INTERACTION, LIMITED-TIME OFFER (LTO), AND HOST ATTRACTIVENESS ON IMPULSIVE BUYING AMONG GEN Z USERS IN THE TIKTOK LIVE SHOPPING FEATURE: (A QUANTITATIVE STUDY IN SURAKARTA CITY) - Riska Kusuma Anjani; Kurniawati Darmaningrum; Atik Lusia (Politeknik Negeri Ambon, 2026)
Introduction: The development of live shopping features on the TikTok platform has changed consumer shopping behavior patterns, especially among Generation Z, by providing an interactive and persuasive shopping experience. This study aims to analyze the influence of Live Interaction, Limited-Time Offer (LTO), and Host Attractiveness on Impulsive Buying among Generation Z users of the TikTok Live Shopping feature in Surakarta City. Methods: This study uses a quantitative approach, employing a survey distributed to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression analysis with the help of IBM SPSS software version 27.Result: The study shows that Live Interaction, Limited-Time Offer, and Host Attractiveness have a positive and significant effect on Impulsive Buying. Intensive direct interaction between the host and the audience can create emotional engagement and social closeness that encourages spontaneous purchasing decisions. In addition, the use of limited-time offers creates a sense of urgency and fear of missing out (FOMO), which accelerates unplanned purchasing decisions. The attractiveness of the host, as reflected in their appearance, communication style, and credibility, also plays an important role in building trust and parasocial relationships with viewers. Conclusion: Simultaneously, these three variables have been proven to significantly influence impulsive buying behavior among Generation Z users on TikTok Live Shopping in Surakarta City. Keywords: Host Attractiveness, Impulsive Buying, Limited-Time Offer, Live Interaction, TikTok Live Shopping